1975
DOI: 10.2307/3279455
|View full text |Cite
|
Sign up to set email alerts
|

Purine and Pyrimidine Transport in Schistosoma mansoni

Abstract: The uptake of purines and pyrimidines by adults of Schistosoma mansoni was studied. Cytosine, thymine, and uracil entered the worms entirely by diffusion. Adenine, guanine, hypoxanthine, and the nucleosides adenosine and uridine were absorbed in part by mediated systems. The results of inhibitor studies suggest the presence of 5 distinct transport sites for these latter compounds. The interaction of adenosine monophosphate with these sites was also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…As shown in Table 1, schistosomes are capable of salvaging pyrimidine nucleobases and nucleosides (Levy and Read, 1975a; Nollen et al, 1976; Mattoccia et al, 1981; Mattoccia and Ciolo, 1983; el Kouni and Naguib, 1990). Thymine, cytosine and orotidine are transported into adult S. mansoni , but not incorporated into their nucleic acids (el Kouni and Naguib, 1990).…”
Section: Uptake Of Pyrimidine Nucleobases and Nucleosidesmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, schistosomes are capable of salvaging pyrimidine nucleobases and nucleosides (Levy and Read, 1975a; Nollen et al, 1976; Mattoccia et al, 1981; Mattoccia and Ciolo, 1983; el Kouni and Naguib, 1990). Thymine, cytosine and orotidine are transported into adult S. mansoni , but not incorporated into their nucleic acids (el Kouni and Naguib, 1990).…”
Section: Uptake Of Pyrimidine Nucleobases and Nucleosidesmentioning
confidence: 99%
“…The second transporter is specific for adenosine. The third transporter has high affinity for adenine but also transports adenosine (Levy and Read, 1975a). Uridine uptake is saturable.…”
Section: Transport Of Pyrimidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their existence was suggested in Clonorchis sinensis, Paragonimus ohirai [10], Mesocestoides corti [2], Schistosoma japonicum [8], S. mansoni [1,12,13], Angiostrongylus cantonensis [18]. The present study suggested that A. costaricensis also possessed a pyrimidine de novo synthetic pathway and salvage pathway.…”
mentioning
confidence: 89%
“…Schistosomes are unable to synthesize purines de novo [16]. The ATP catabolic pathway that is driven by SmATPDase1action in the external environment of the intravascular worms may yield purine derivatives in their vicinity that can then be easily imported from the host bloodstream [17].…”
Section: Introductionmentioning
confidence: 99%